The environmental sustainability of meat-based versus vegan pet food - Billy Nicholles; Billy Nicholles; Andrew Knight; Andrew Knight; Andrew Knight; Andrew Knight (Frontiers in Sustainable Food Systems)
Rapid climate change is one of humanity’s most pressing global challenges, and we must urgently address unsustainable practices in all sectors to mitigate its most devastating effects. The pet food sector is a large and growing global industry that feeds about one billion dogs and cats. Moreover, its production is closely linked to the livestock sector, to which at least 25% of all anthropogenic greenhouse gas (GHG) emissions to date are attributable, and probably substantially more. Globally, dogs and cats consume 9% of livestock animals. In the US, this rises to 20%. This review collates and analyses studies on the environmental impacts of pet food, and recommends mitigation strategies. All reviewed studies agree that pet food is associated with at least non-negligible environmental impacts that must be accounted for and addressed: in the US, 25–30% of the environmental impacts of animal production have been attributed to companion animal diets. Studies have estimated a wide range of environmental “paw prints” for dog and cat diets; in some cases, the environmental impacts of some canine diets compare to or exceed those of human diets. Within pet food, ingredient selection is the most important factor. The most effective measure we can currently take to mitigate these impacts is to transition to non animal-based (vegan) pet food, where this has been formulated to be nutritionally sound. Such a transition could achieve very significant GHG and land use savings. In wealthy nations with high rates of companion animal guardianship, the benefits of this transition are demonstrably equivalent to one quarter to one third of the environmental benefits achievable through human dietary change. A transition to nutritionally sound vegan pet food represents a significant extant climate change mitigation strategy which warrants immediate implementation.